Comparative Study on Micro and Nano Sized SiC Particulates Reinforced Al7075 Composites using Stir Casting Process - M. Ravikumar; H.N. Reddappa; R. Suresh; E.R. Babu; C. Reddy Nagaraja (Archives of Metallurgy and Materials)
This paper is designed to investigate the wear and mechanical characterization of metal matrix composites (MMCs) by using micro and nano SiC on Al to study the influence of micro/nano SiC on the properties of fabiricated composite. Micro and nano-composites with 1-4% of SiCp were developed using stircasting processes. From the outcomes, an improved grain refinement of micro and nano-composites when compared to monolithic was seen from the microstructural study. It found that an increase in SiC particulates content caused enhanced mechanical properties. Though, nano SiC reinforced MMCs resulted in improved mechanical properties compared to micro sized SiC particulates reinforced MMCs. The wear study was evaluated for comparison of micro/nano MMCs. The investigation indicates that, wear resistance of nano composites is better as compared to micro-SiCp reinforced MMCs. Fractured surfaces were inspected by the SEM analysis to study the nature of fracture in the micro and nano composite samples.